Optimalisasi Biaya Persediaan Bahan Baku Ijuk Dengan Pendekatan Metode Economic Order Quantity di UMKM Rinjanni Ciamis - andriani; Tri Ngudi Wiyatno (Journal of Optimization System and Ergonomy Implementation, 2025)
Material inventory plays an important role in supply chain management because it affects the continuity of the production process and the quality of the products produced. The main problem faced by UMKM Rinjanni Ciamis is the high cost of inventory due to excessive ordering frequency. In addition, this UMKM has not implemented reorder points or safety stock as part of inventory control. One method that can be used to reduce total inventory costs is Economic Order Quantity (EOQ). The EOQ method is a mathematical approach that aims to determine the optimal order quantity so that total inventory costs, both ordering and storage costs, can be minimized. Based on the calculations, the total inventory costs of this UMKM using the conventional method were Rp 4.422.000, while the application of the EOQ method reduced the costs to Rp 278.795, resulting in savings of 94% or Rp 4.143.205. In addition, the EOQ method was also able to determine a safety stock of 258 kg and a reorder point of 790 kg, whereas in the previous conventional method, these two parameters had not been applied. Thus, the application of EOQ can improve inventory control efficiency and reduce operational costs at UMKM Rinjanni Ciamis.